2015
DOI: 10.1002/adhm.201500177
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress in Nanotechnology Applications for Diagnosis and Treatment of Kidney Diseases

Abstract: Significant progress has been made in nanomedicine, primarily in the form of nanoparticles, for theranostic applications to various diseases. A variety of materials, both organic and inorganic, have been used to develop nanoparticles with promise to achieve improved efficacy in medical applications as well as reduced systemic side effects compared to current standard of care medical practices. In particular, this article highlights the recent development and application of nanoparticles for diagnosing and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 128 publications
(95 reference statements)
0
11
0
Order By: Relevance
“…The filtration initially occurs at the interface of glomerulus and Bowman’s capsule. Filtered molecules or nanoparticles need to pass through three filtration layers, the endothelium, glomerular basement membrane (GBM), and foot processes of the podocytes [79]. The endothelium provides an initial physical barrier that contains a pore size of 80–100 nm in diameter.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The filtration initially occurs at the interface of glomerulus and Bowman’s capsule. Filtered molecules or nanoparticles need to pass through three filtration layers, the endothelium, glomerular basement membrane (GBM), and foot processes of the podocytes [79]. The endothelium provides an initial physical barrier that contains a pore size of 80–100 nm in diameter.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Recently, gold nanoparticles have been commonly applied for surface plasmon resonance scattering since they can resonantly scatter visible and near-infrared light due to their surface plasmon oscillation [ 78 ]. In addition, they are easy to prepare, readily bioconjugated, and have low cytotoxicity, making them suitable for biomolecular labeling and targeting [ 79 ]. It is reported that the conjugated nanoparticles tended to aggregate together, inducing a greatly enhanced surface plasmon resonance scattering compared to unconjugated nanoparticles [ 80 ].…”
Section: Nanotechnology-based Detection and Diagnostic Methodsmentioning
confidence: 99%
“…In the past few decades, nanotechnology has brought new techniques to cancer diagnosis [ 36 , 38 , 132 , 133 ]. The performance parameters of nanoparticles-such as biocompatibility, function-specific size and shape, blood circulation half-life, and targeting to specific cell surface molecules-can be controlled by modulating their fabrication materials, methods or surface chemistry, making nanoparticles a promising diagnostic material [ 79 ]. The present review article has critically introduced nano-based detection strategies for oral cancers, and summarized various kinds of nanomaterials, sample types, and the characteristic of each technique in Table 1 .…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…In the case of iron (Xu et al, 2014;Baiu et al, 2015) and gold anti-GD2 NPs (Jiao et al, 2016), the authors concurred with high tumor specificity targeting and suggested the use of anti-GD2 NPs not only as anticancer nanomedicines per se but also as suitable diagnostic nanodevices in NB therapy. Theragnosis (simultaneous diagnosis and treatment) is nowadays gaining relevance in nanotechnology (Lee et al, 2015). Given that metallic NPs can be monitored by MRI, they might be very useful in NB, where diagnosis and staging are crucial (Chen et al, 2018a).…”
Section: Targeted Nanomedicines For Neuroblastomamentioning
confidence: 99%